Redescription of ancistrus greeni (Siluriformes: Loricariidae), and description of a new species from the río madre de dios basin, peru - Bifi, Alessandro Gasparetto; Ortega, Hernán (Neotropical Ichthyology, 2020)
A new species of Ancistrus is described from minor tributaries of the río Madre de Dios basin (Cusco-Madre de Dios-Puno), in Peru. The new species shares with A. greeni an uncommon unicusp dentition; but it is distinguished from A. greeni by a larger orbital diameter, deeper caudal peduncle, and larger adipose-fin spine. The redescription of A. greeni is provided, and its recognition along with the discovery of this new species increases to five the officially number of Ancistrus species from the río Madre de Dios basin. The lectotype and paralectotype of A. greeni are provided. © 2020 The Authors. Diversity and Distributions Published by SBI.
Keywords: Amazon Basin; Ancistrini; Armored catfish; Río Inambari basin; Taxonomy